Recent development of antiviral nano-coatings for COVID-19 management - a review. (14th November 2022) - Raula, Manoj; Sengupta, Sucheta
Global pandemic COVID-19 has affected almost the entire world population in every aspect of life in terms of health, environment, and economy. According to WHO, the main source of transmission of this deadly virus (SARS-CoV-2) is proven to be through the aerosol coming from the infected person's cough, sneeze, or exhalation. These aerosols are likely to settle down on the exposed surfaces and such infected surfaces are known to be potential source of contamination. The spread of the viral infections can be controlled in a great extent with the development of anti-viral nano-coating materials for various surfaces. Thus, development of such anti-viral nano-coating materials becomes increasingly popular amongst the researchers due to their extensive applications on surfaces, such as, glass, cotton, plastic and many more. In this short review, we will describe a summary of the popular metals and metal oxide nanomaterials commonly explored as antiviral coatings to control the spread of various viral disease along with the corresponding working principle and effectivity of such coatings.